Action Research for Creating Social Innovation in the Employment of People with Disabilities: Useing Systems Thinking (Case Study: Salam Social Innovation Center) - Ali Asghar Sad Abadi; Neda Aramipour; Kiarash Fartash (توسعه اجتماعی, 2021)
In a society where all people can use their capacity and enjoy equal opportunities, there is collective joy and spirit, and this feedback comes back to the community and enhances social participation, capital, and solidarity. In addition, it can make the country grow and develop, but, as we know, disability in some societies limits people and they cannot even find a suitable job. On the other hand, according to statistics and evidence, the unemployment rate of people with disabilities is on the rise and unemployment causes many problems for them. Numerous organizations and companies have taken steps to solve the employment problem of these people, and even some of these companies were start-ups created by some of the disabled, but this problem still remains unresolved. In this research, we seek to investigate the problem and provide some solutions. After reviewing the issue, we conducted this study at Salam Social Innovation Center. At first, the model was implemented through using the four-stage model of David Peter Stroh. Interviews were conducted with related people and stakeholders and then data were analyzed by using action research methodology. Suggestions were also provided in two parts: quick fixes and fundamental solutions. In the quick-fix solution section, some actions can solve the problem cross-sectionally (such as the government's requirement to hire the disabled or pay them pensions), but the key to solving this problem is to pay attention to these people's special abilities and not to their disabilities.